2018
DOI: 10.1016/j.jbiomech.2018.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of osteochondral impact with cushioning and graft Insertion: Cartilage damage is correlated with delivered energy

Abstract: Articular cartilage is susceptible to impact injury. Impact may occur during events ranging from trauma to surgical insertion of an OsteoChondral Graft (OCG) into an OsteoChondral Recipient site (OCR). To evaluate energy density as a mediator of cartilage damage, a specialized drop tower apparatus was used to impact adult bovine samples while measuring contact force, cartilage surface displacement, and OCG advancement. When a single impact was applied to an isolated (non-inserted) OCG, force and surface displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…It could be found that the impact modulus and impact energy of bicontinuous hydrogel are superior to the NBR rubber and cartilage. 47,48…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be found that the impact modulus and impact energy of bicontinuous hydrogel are superior to the NBR rubber and cartilage. 47,48…”
Section: Resultsmentioning
confidence: 99%
“…It could be found that the impact modulus and impact energy of bicontinuous hydrogel are superior to the NBR rubber and cartilage. 47,48 Fig. 5 Schematic illustrations of the mechanism of hierarchical energy dissipation in the bicontinuous hydrogel.…”
Section: Dynamic Impact Resistant Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…There are several limitations to the present study. First, in addition to the magnitude of load, injuries would also be affected by loading rate 31–33 , which cannot be separated in the present drop‐tower impacting configuration. Therefore, the rabbit model cannot completely simulate motor vehicle dashboard‐type injury.…”
Section: Discussionmentioning
confidence: 99%
“…Longer grafts were found to require an increased number of insertional impacts and cumulative impact force detrimental to surface chondrocyte viability and graft survival. [12][13][14] Studies exist evaluating the biomechanical properties of OCAs of 7 mm in depth and longer, but no study has clearly defined the minimal graft depth required to resist deforming forces. [15][16][17] Deforming forces leading to graft protrusion or subsidence of more than 1 mm can lead to unfavorable outcomes and fibrocartilaginous, rather than osteochondral incorporation.…”
mentioning
confidence: 99%